Cognitive impairments in patients with low grade gliomas and high grade gliomas - Eliane C. Miotto; Aluizio Silva Junior; Clemar Corrêa Silva; Hector Navarro Cabrera; Melissa A.R. Machado; Glaucia R.G. Benute; Mara C.S. Lucia; Milberto Scaff; Manoel Jacobsen Teixeira (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The relationship between brain tumors and cognitive deficits is well established in the literature. However, studies investigating the cognitive status in low and high-grade gliomas patients are scarce, particularly in patients with average or lower educational level. This study aimed at investigating the cognitive functioning in a sample of patients with low and high-grade gliomas before surgical intervention. METHOD: The low-grade (G1, n=19) and high-grade glioma (G2, n=8) patients underwent a detailed neuropsychological assessment of memory, executive functions, visuo-perceptive and visuo-spatial abilities, intellectual level and language. RESULTS: There was a significant impairment on verbal and visual episodic memory, executive functions including mental flexibility, nominal and categorical verbal fluency and speed of information processing in G2. G1 showed only specific deficits on verbal and visual memory recall, mental flexibility and processing speed. CONCLUSION: These findings demonstrated different levels of impairments in the executive and memory domains in patients with low and high grade gliomas.